2007
DOI: 10.1021/jp065302n
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of π−π Tunneling in [2]Rotaxane Molecular Electronic Switches

Abstract: We perform large-scale density functional and matrix Green's function calculations, and study the coherent charge tunneling properties of molecular electronic devices based on the central part of [2]rotaxane molecules. We extract molecular core regions from realistic monolayer configurations with folded molecular structures and sandwich them between Au(111) electrodes to form device models. We show that the electrical switching behavior can be observed within the π-π stacked serial arrangement of redox-active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The ferrocenyl group shifts from 4.15 to 4.28 ppm (Δδ = 0.13 ppm). All of these changes are ascribed to the multiple molecular interactions occurring in close proximity, including π–π stacking between the phenyl and ferrocenyl groups and the C–H···π effect that occurs when the ferrocenyl group and dipyridinium cation are alongside each other. Consequently, we envision the possible chemical structure of the 1:1 mixture in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The ferrocenyl group shifts from 4.15 to 4.28 ppm (Δδ = 0.13 ppm). All of these changes are ascribed to the multiple molecular interactions occurring in close proximity, including π–π stacking between the phenyl and ferrocenyl groups and the C–H···π effect that occurs when the ferrocenyl group and dipyridinium cation are alongside each other. Consequently, we envision the possible chemical structure of the 1:1 mixture in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of this paper is to provide such validation. Previously, we investigated these compounds using a multiscale first principles approach combining quantum mechanics (QM) and atomistic force field (FF) methods. First we considered the molecules as individual species, and then we examined self-assembled monolayers bound to gold surfaces or compressed into Langmuir monolayers at the air−water interface. These studies successfully predicted a number of phenomena that were confirmed later experimentally, including the higher conductivity of the DNP relative to the TTF, and the increased stability of the TTF relative to the DNP (by 2.0 kcal/mol from QM, 2.3 kcal/mol from the FF, and 1.4−1.6 kcal/mol from experiment). , In addition, on the basis of the predicted footprint of the 115 Å 2 /molecule for the self-assembled structure, we predicted that the surface tension of the TTF is 32% lower than that of the DNP, an observation that was confirmed in subsequent experiements. , …”
Section: Introductionmentioning
confidence: 99%
“…Previously, we investigated these compounds using a multiscale first principles approach combining quantum mechanics (QM) and atomistic force field (FF) methods. First we considered the molecules as individual species, and then we examined self-assembled monolayers bound to gold surfaces or compressed into Langmuir monolayers at the air−water interface. These studies successfully predicted a number of phenomena that were confirmed later experimentally, including the higher conductivity of the DNP relative to the TTF, and the increased stability of the TTF relative to the DNP (by 2.0 kcal/mol from QM, 2.3 kcal/mol from the FF, and 1.4−1.6 kcal/mol from experiment). , In addition, on the basis of the predicted footprint of the 115 Å 2 /molecule for the self-assembled structure, we predicted that the surface tension of the TTF is 32% lower than that of the DNP, an observation that was confirmed in subsequent experiements. , …”
Section: Introductionmentioning
confidence: 99%
“…In this work, the transport properties of an isolated Stoddart‐Heath‐type rotaxane in these two coconformations of its neutral state were explored. The transport properties of rotaxane molecular junctions are also known to be influenced by the molecule‐electrode interface . This dependence of the transport properties on the rotaxane/electrode interface is presumably relatively independent of coconformation and is not included in this work.…”
Section: Discussionmentioning
confidence: 99%